Early interventions and disability insurance: Experience from a field experiment - Per Engström; Pathric Hägglund; Per Johansson (Institute for the Study of Labor (IZA), 2012)
This paper estimates the effects of early interventions in the Swedish sickness insurance system. The aim of the interventions is to screen and, further to, rehabilitate sick listed individuals. We find that the early interventions - in contrast to what is expected - increase the inflow into disability benefits by around 20 percent. In order to explain the results, we develop a simple theoretical model based on asymmetric information of the health status. The model predicts that the treatment effect is larger for individuals with low incentives to return to work. In order to test this prediction we estimate effects for sick listed employed and unemployed separately. Consistent with the model's prediction, we find that the effect is larger for the unemployed than for the employed.
urn:nbn:de:101:1-201301212132
Keywords: C93; H51; H55; I18; J22; 330; monitoring; screening; vocation rehabilitation; disability insurance; sickness insurances; unemployment insurance; randomized experiment; Rehabilitation; Erwerbsunfähigkeitsrente; Gesetzliche Krankenversicherung; Asymmetrische Information; Feldforschung; Schweden